Muslims through Storytelling: Islamic Law, Culture and Reasoning in South Sulawesi - Alimi, Moh Yasir (KOMUNITAS: International Journal of Indonesian Society and Culture, 2018)
This article explores the use of storytelling by the Muslims of South Sulawesi in their efforts to confront the formalization of Islamic law in the province. My specific objective is to nuance the existing approach to Islam and Muslim life, which to date focuses on scriptural argumentation, or analytical reasoning based on the Quran and other Islamic sources. The exclusive focus on scriptural argumentation as the main approach to explain Islam does not help us to understand how Muslims use non-analytical forms of human communication in response to shari’a formalization. The experiences of Muslims in South Sulawesi demonstrates that storytelling can be a meaningful and direct means to express Islamic identity and to challenge the formalization of shari’a. In the hierarchies of reasoning used in South Sulawesi by Muslims, scriptural argumentation is not the most important